Postoperative Mobilization After Superior Rotator Cuff Repair: Sling versus No-sling. A Randomized Controlled Trial: Sling versus no-sling after RCR. Issue 5 (31st May 2019) - Tirefort, Jérome; Schwitzguebel, Adrien J.; Collin, Philippe; Nowak, Alexandra; Plomb-Holmes, Chantal; Lädermann, Alexandre
Objectives: Patients are commonly advised to wear a sling for 4–6 weeks after rotator cuff repair (RCR) despite negative effects of early immobilization and benefits of motion rehabilitation. The study aimed to compare clinical and radiographic outcomes up to 6 months following RCR with sling immobilization and without sling immobilization. Methods: We randomized 80 patients scheduled for arthroscopic repair of small or medium superior rotator cuff tears into 2 equal groups: 'sling' and 'no-sling' groups. Passive mobilization was performed in both groups during the first 4 postoperative weeks followed by a progressive active mobilization. Patients were evaluated clinically at 10 days, 1.5, 3 and 6 months, and using ultrasound at 6 months. Uni- and multi-variable analyses were performed to determine if postoperative scores are associated with gender, age at surgery, immobilization, arm dominance, biceps procedure, resection of the distal clavicle, as well as preoperative scores. Results: The two groups had similar preoperative patient characteristics, function, or adjuvant procedures. At 10 days, there was no difference in pain among the two groups (5.2±2.3 vs 5.2±1.9, p=0.996). In comparison to the sling group, the no-sling group showed greater external rotation (23.5±15.6 vs 15.3±14.6, p=0.017) and active elevation (110.9±31.9 vs 97.0±25.0, p=0.038) at 1.5 months, as well as better active elevation (139.0±24.7 vs 125.8±24.4, p=0.015) and internal rotation (>T12 in 50% vs 27.5%, p=0.011) at 3 months. Ultrasound revealed no differences at 6 months in tendon thickness anteriorly (p=0.472) or posteriorly (p=639), bursitis (p=1.000), echogenicity (p=0.422), or repair integrity (p=0.902). Multi-variable analyses confirmed that ASES score increased with patient age (beta, 0.60; p=0.009), SANE decreased with sling immobilization (beta, -6.3; p =0.014), and that pain increased with sling immobilization (beta, 0.77; p =0.022). Conclusion: No immobilization after RCR is associated with better early mobility and functional scores in comparison to sling immobilization. Postoperative immobilization with slings may therefore not be required for patients treated for small or medium tears.